Family Factors Associated with Consumption of Spirits: A Comparative Gender-Based Study of Ugandan Students in Public Secondary Schools - Rukundo, Aloysius; Ayebare, David Santson; Kibanja, Grace; Steffens, Karl (Education Research International, 2020)
This study aims at investigating family factors associated with consumption of spirits across gender of students in public secondary schools in Uganda. A cross-sectional survey using self-administered questionnaires was used to collect data on consumption of sprits in the past 12 months prior to the study. Of the 1,591 students recruited, the overall prevalence of consumption of spirits was found to be 17.3% (n = 275) with higher consumption of spirits among males (20.3%). Results indicate that unemployed heads of families (aOR =2.5, 95% CI: 1.30–4.76, p < 0.01), fairly religious (aOR =2.7, 95% CI: 1.08–6.49, p < 0.05), and not religious families (aOR =2.9, 95% CI: 1.17–7.11, p < 0.05) were factors associated with consumption of spirits. Early prevention of consumption of spirits could be focused on male students, fathers’ occupation, and family religiosity. In addition, school administrators and authorities could consider these factors during routine school inspections to guard discipline among students in Uganda.
Keywords: Consumption of Spirits; Gender-Based; Students in Public Secondary Schools